Pertussis and pertussis-like syndrome in young children - I. V. Babachenko; N. S. Tian; Yu. V. Nesterova (LLC "Diagnostics and Vaccines", 2021)
The most common infectious diseases with a risk of severe, non-smooth course and unfavorable outcome in young children, including the first year of life, are pertussis and respiratory syncytial viral infection (RSV infection), often occurring with pertussis-like syndrome.Objective: to establish clinical and laboratory differential diagnostic criteria for pertussis and RSV infection in children of the first year of life.Materials and methods: A retrospective comparative study was conducted, which included patients of the first year of life (from 1 month to 11 months and 29 days), regardless of the duration of hospitalization and duration of the disease: 48 patients with pertussis and 26 with acute RSV infection.Results: The compared groups of patients were comparable in age, the number of severe forms (4.6 ± 0.5 months, 17% for pertussis and 4.0 ± 0.2 months, 16% for RS infection). The disease in both cases began subacute, however, with RSV infection 92% of children were hospitalized in the first 5 days from the onset of the disease, with pertussis - in the first week of the period of convulsive cough - 47.9%, in the second week - 41.7%, in the third week - 10.4%. 52% of patients with RSV infection had no fever or (in 32%) did not exceed 1-3 days. In 41.3% of patients it was subfebrile (37-38 °C), in 21.1% it was febrile (38-39 °C). In patients with pertussis the onset of the disease took place against the background of normal body temperature. In patients with RSV infection, bronchiolitis was recorded in 24% of cases, obstructive bronchitis - in 60%. Patients with pertussis, 89.6% of whom were not vaccinated and 10.4% did not complete the initial course of vaccination, had a typical paroxysmal cough with reprises. Complications in the form of respiratory rhythm disturbances were recorded in 14.6% of cases, pneumonia - in 6.3%. Comparison of hematological parameters revealed highly significant differences in the levels of leukocytosis and relative lymphocytosis (p < 0.001), as well as thrombocytosis (p < 0.01), with the predominance of all indicators in patients with pertussis.Conclusion. Differential diagnostic criteria for the similarity of the clinical picture may be established hematological differences: pronounced leukocytosis due to lymphocytosis, increasing in dynamics, and thrombocytosis in pertussis and normocytosis with moderate lymphocytosis, a possible tendency to thrombocytosis in severe RSV infection.